Characterization of Optimized TiO2 Nanotubes Morphology for Medical Implants: Biological Activity and Corrosion Resistance - Nogueira, Ricardo Pereira; Uchoa, Jose Deuzimar; Hilario, Fanny; Santana-Melo, Gabriela de Fatima [UNESP]; Reis de Vasconcellos, Luana Marotta [UNESP]; Marciano, Fernanda Roberta; Roche, Virginie; Jorge Junior, Alberto Moreira; Lobo, Anderson Oliveira (Dove Medical Press Ltd, 2021)
Background: Nanostructured surface modifications of Ti-based biomaterials are moving up from a highly-promising to a successfully-implemented approach to developing safe and reliable implants. Methods: The study's main objective is to help consolidate the knowledge and identify the more suitable experimental strategies related to TiO2 nanotubes-modified surfaces. In this sense, it proposes the thorough investigation of two optimized nanotubes morphologies in terms of their biological activity (cell cytotoxicity, alkaline phosphatase activity, alizarin red mineralization test, and cellular adhesion) and their electrochemical behavior in simulated body fluid (SBF) electrolyte. Layers of small-short and large-long nanotubes were prepared and investigated in their amorphous and crystallized states and compared to non-anodized samples. Results: Results show that much more than the surface area development associated with the nanotubes' growth; it is the heat treatment-induced change from amorphous to crystalline anatase-rutile structures that ensure enhanced biological activity coupled to high corrosion resistance. Conclusion: Compared to both non-anodized and amorphous nanotubes layers, the crystallized nano-structures' outstanding bioactivity was related to the remarkable increase in their hydrophilic behavior, while the enhanced electrochemical stability was ascribed to the thickening of the dense ruble barrier layer at the Ti surface beneath the nanotubes.
Keywords: surface modification; TiO2 nanotubes; commercially pure titanium; bioactivity